Formation of mixed X,n-radiation field at an electron accelerator - Zakharchenko, A.A.; Uvarov, V.L.; Malets, Eu.B. (Problems of Atomic Science and Technology, 2022)
For conducting photonuclear programs with the use of a high-intensity photon source the latter is ordinary obtained by transformation of an electron beam into X-ray radiation. Such a process is performed using an intermediate target-converter maid from a high-Z material. The (γ,n) reactions take place in the converter under the action of high-energy bremsstrahlung photons. As a result, a quasi-isotropic neutron flux escapes the converter jointly with the photon beam directed forward. The parameters of the both types of radiation, as well as the ratio of their intensities play the important role depending on a program under way. In work, the spatial radiant characteristics of the mixed X,n-radiation generated with the electron beam in the converter located together with an isotopic target in the middle of a neutron moderator in the electron energy range 40…95 MeV and various size of the moderator are studied by computer simulations with the use of a GEANT4 transport code. Для виконання фотоядерних програм з використанням джерела фотонів великої інтенсивності останнє зазвичай одержують шляхом трансформації пучка електронів у гальмівне випромінення. Цей процес здійснюють за допомогою проміжної мішені-конвертера, який виготовляють з матеріалу з великим Z. Під дією високоенергетичних гальмівних фотонів у конвертері відбуваються (γ,n)-реакції. Як результат, з нього, крім спрямованого уперед потоку фотонів, виходить також квазіізоторопний потік нейтронів. Параметри обох видів випромінення, так само як і співвідношення їх інтенсивностей, грають важливу роль залежно від програми, що виконується. У роботі методом комп’ютерного моделювання з використанням транспортного коду GEANT4 досліджено просторово-енергетичні характеристики мішаного X,n-випромінення, яке генерується електронним пучком у конвертері з танталу, що розміщений разом з ізотопною мішенню у середині модератора нейтронів, при енергії електронів у діапазоні 40…95 МеВ і різному розмірі модератора.